2012
DOI: 10.1103/physrevlett.108.037203
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Dynamics of the Collinear-to-Spiral Antiferromagnetic Phase Transition in CuO

Abstract: We report on the ultrafast dynamics of magnetic order in a single crystal of CuO at a temperature of 207 K in response to strong optical excitation using femtosecond resonant x-ray diffraction. In the experiment, a femtosecond laser pulse induces a sudden, nonequilibrium increase in magnetic disorder. After a short delay ranging from 400 fs to 2 ps, we observe changes in the relative intensity of the magnetic ordering diffraction peaks that indicate a shift from a collinear commensurate phase to a spiral incom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 36 publications
(37 reference statements)
2
85
2
Order By: Relevance
“…Residual diffraction peak intensity for even the highest fluence is likely a result of a small misalignment between pump and probe beams and relatively similar spot sizes. At low fluences, the decay time appears to be nearly constant, but then decreases as the decay amplitude saturates with complete melting of the long-range magnetic order; extracted time constants range from 22.4 ps at the lowest fluence to 7.5 ps at the highest fluence, much slower than time constants of <1 ps recorded for melting of magnetic order in other materials [10,12,16]. …”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Residual diffraction peak intensity for even the highest fluence is likely a result of a small misalignment between pump and probe beams and relatively similar spot sizes. At low fluences, the decay time appears to be nearly constant, but then decreases as the decay amplitude saturates with complete melting of the long-range magnetic order; extracted time constants range from 22.4 ps at the lowest fluence to 7.5 ps at the highest fluence, much slower than time constants of <1 ps recorded for melting of magnetic order in other materials [10,12,16]. …”
Section: Resultsmentioning
confidence: 72%
“…Time-resolved resonant X-ray diffraction has been used to probe ultrafast changes in magnetic order in several oxides [10][11][12][13]. For example, we have recently shown that THz excitation can resonantly drive a magnon, which leads to a tilt of the spin cycloid structure in TbMnO3 due to magnetoelectric coupling [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, extensive studies have been reported by the Oxford group. [28][29][30] Structure and properties:. The lattice structure of CuO is illustrated in Figure 1 and its magnetic cycloidic spin arrangement in Figure 2.…”
Section: Copper Oxidementioning
confidence: 99%
“…This advantage has been recently employed to trigger ultrafast spin dynamics and spin reorientation in antiferromagnets. [7][8][9][10] Combining these two different classes of materials in a FM/AFM heterostructure could thus produce a composite material with novel dynamical properties.…”
Section: Introductionmentioning
confidence: 99%